External Shariah Audit in Financial Services Industry: Practitioners’ View on Its Merits, Scope and Implementation Challenges - Nurazalia Zakaria; Zurina Shafii; Supiah Salleh (Universiti Sains Islam Malaysian, 2024)
Page : 21-24